Changing Healthcare: Discovering Advances in Telehealth from the World Congress, Torre del Mar 2022 - Muñoz-Cruzado y Barba, Miguel (Revista Española de Comunicación en Salud, 2023)
The 1st World Telehealth Congress took place in Torre del Mar (Malaga) in 2022. It was organised by the Spanish Association of Health Communication and brought together participants from 43 countries. The congress included round tables on topics such as Tele-Pharmacy, Cybersecurity in Health, Tele-Nursing, Tele-Physiotherapy, TeleOccupational Therapy and Tele-Psychology. The conclusions highlighted key aspects. In Tele-Pharmacy, the need to improve the use of the pharmaceutical network and the implementation of the E-prescription was pointed out. In Tele-Occupational Therapy, the importance of ICTs to get closer to people’s health needs and to promote empowerment and training was highlighted. In Tele-Medicine, it was emphasised that care must be human, and the risks and benefits of new technologies were addressed. In Tele-Nursing, the usefulness of ICTs as a complementary tool was mentioned, but the digital divide and data protection were cautioned against. In TelePhysiotherapy, the benefit of ICTs in patient assessment and treatment was highlighted. In Tele-Psychology, the advantages and disadvantages of remote psychological care were discussed. Overall, the congress highlighted the potential of new technologies in healthcare, but also pointed out challenges and areas for improvement.
Keywords: telehealth; telemedicine; eHealth; artificial intelligence; congress